Antianginal medications and long‐term outcomes after elective catheterization in patients with coronary artery disease. Issue 12 (December 2016) - Shen, Lan; Vavalle, John P.; Broderick, Samuel; Shaw, Linda K.; Douglas, Pamela S.
Abstract : Background: Antianginal medications are a class I recommendation by the American College of Cardiology/American Heart Association guidelines for stable ischemic heart disease. We sought to better understand guidance in drug selection and real‐life outcomes of antianginal medication use. Hypothesis: In patients with stable ischemic heart disease, antianginal medications lower mortality. Methods: We evaluated 5608 patients with obstructive coronary artery disease (CAD) on elective cardiac catheterization with follow‐up through self‐administered questionnaires. Patients were classified as being prescribed a particular medication if they received that medication at index catheterization, or within 3 months postcatheterization. The association between antianginal medication use and outcomes was evaluated using Cox proportional hazards models. Results: Compared with the 11% not prescribed any antianginal medication, patients prescribed antianginal medication were more likely to be older and female; have a history of hypertension, diabetes mellitus, peripheral vascular disease, or 3‐vessel CAD; have lower adjusted mortality (hazard ratio [HR]: 0.75, 95% confidence interval [CI]: 0.63‐0.89); and experience mortality or myocardial infarction (HR: 0.83, 95% CI: 0.71‐0.98). Compared with patients not taking β‐blockers (17%), those taking β‐blockers had a lower risk of mortality (HR: 0.76, 95% CI: 0.66‐0.88). Patients prescribed calcium channel blockers or long‐acting nitrates had a higher risk of mortality compared with nonusers (HR: 1.16, 95% CI: 1.04‐1.29; HR: 1.20, 95% CI: 1.08‐1.34; respectively). Conclusions: Antianginal medications are not universally prescribed among obstructive CAD patients; nonuse was associated with higher mortality. For CAD patients with or without prior myocardial infarction, β‐blockers were associated with improved long‐term survival.